The Armament, Material and Technical Equipment of the Engineering Units of the Polish Army in the years 1945–2010 - Pietrygała, Robert (Tools of War, 2023)
The factor of material and technical equipment had a significant impact on the combat capability of military components, in addition to matters such as education and training of personnel training. In the entire post-war period, there was a significant progress and qualitative development in science, which influenced the search for newer and better technical solutions. This scientific and technical progress was very often used in military technology, especially in engineering troops. This was most visible in the technical equipment. The article discusses the above-mentioned aspects of the armament and the material technical equipment of the engineering units of the Polish Army in the years 1945-2010. The article is divided into three main parts: the first part describes the armaments used by the engineering troops, the second one presents technical engineering equipment in detail, and the third part contains information on material equipment. The article is supplemented witch numerous tables and lists of the equipment used.